Theme centered interaction in critical vocational teacher education: An introduction into an ethical founded method and model to strengthen self-reflexive autonomy and socially responsible action - Franz Xaver Kaiser (International Journal for Research in Vocational Education and Training (IJRVET), 2018)
Context: The train of thoughts in this contribution is situated in the VET teacher training on an academic level, as it is usual in Germany. Key issue is the pedagogical qualification of the VET teachers and the question of how to give them possibilities to reflect their own biography, their interdependences to the actual cultural and economic environment and their way to choose the pathway to become a VET teacher. How to enable them to argue with their values, fears, strength and weaknesses in their life and especially in leading groups, as they will have to do in classroom management. And at least how to give them an idea of an emancipative, critical and participative way of forming learning situations in which they feel sure and lively to encourage the apprentices and learners in schools to act autonomic and critical in work and besides. This is necessary because of the changes in work and VET in the recent centuries with consequences for workers, learners and curricula as well as the contradictions in that process. Approach: The transformation and the liberalisation of markets and changes of work organisation, the enlargement of tasks in the occupations adds greater meaning to social knowledge and competences, the ability for teamwork and personal development in vocational education. To develop this ability Theme-Centered Interaction (TCI), as a humanistic-psychological approach is used and combined with Critical-Subject-Oriented Vocational Education Theory, inspired by the Critical Theory of the Frankfurt School. VET-teacher students learn in theory and practice to shape their own way to lead themselves and the pupils in the class and to reflect their activities in a critical way of thinking. The paper ends with brief description of seminar lectures with VET teacher students at the University of Rostock where TCI is practiced as one example how we can reach the objectives described before. Findings: The TCI-concept is helpful to set up better teamwork and self-reflection in the group of the learners. It's a useful way to prepare them for their practical school phase in which TCI is used as reflection model as well. Key message: Universities as learning places in the tradition of enlightenment have to open up spaces in VET teacher development for domination-free communication and participatory learning within the framework of university studies, which can create a distance to a given social reality, enables students to dissociate from collectively developed goals to become critical formers of their working life and teaching.
Keywords: 330; VET; Vocational Education and Training; Vocational Teacher Students; Communication Skill; Critical Thinking Skill; Interpersonal Competence; Curriculum Development